Effect of Nano Zinc Supplementation on Hematological Parameters and Body Condition Score During Transition Period in Sahiwal Cows - Nandanwar, Arvind Kumar; Bhonsle, Dhirendra; Prusty, Sonali; Rajendran, D.; Thakre, Ankita (Indian Journal of Animal Nutrition, 2022)
The objective of the present study was to investigate the effect of nano zinc oxide in comparison to inorganic Zn on hematology and body condition score in Sahiwal cows during transition period. A total of 24 Sahiwal cows were randomly divided into four groups (control, Zn40, nanoZn20 and nanoZn40) with 6 animals in each, based on parity (2-5 parity). Basal diet was followed in all the groups whereas in groups Zn40, nanoZn20 and nanoZn40 additional 40 ppm Zn from ZnO, and 20 and 40 ppm Zn from nano ZnO was supplemented, respectively. Results indicated that prepartum and postpartum mean values of TEC, Hb and PCV were significantly (P≤0.01) higher in nanoZn20 group compared to other groups. Concentration of TLC was increased subsequently from 2nd weeks before calving until the day of calving and then decreased, however, mean values of TLC was found to be higher in nanoZn20 group. The lymphocyte and neutrophil per cent were higher and lower, respectively during prepartum compared to postpartum period. Significantly lower value of neutrophil was found on the day of calving in nanoZn40. Monocyte, eosinophil and basophil levels were found similar in all groups throughout transition period, however, monocyte per cent was significantly higher at 21 days postpartum in nanoZn20 group. There was no significant difference in mean BCS during prepartum and postpartum, though numerically it was higher during prepartum compared to postpartum period. There was maximum reduction in BCS from 21 days prepartum to 21 days postpartum in control group compared to that of Zn40, nanoZn40 and nanoZn20 groups. Body condition score of Sahiwal cow was better in nanoZn20 group. Sahiwal cows supplemented with 20 ppm nano Zn showed better hematological profile and BCS compared to unsupplemented and other 40 ppm nano Zn or inorganic Zn supplemented groups.